Retinal and Cortical Blood Flow Dynamics Following Systemic Blood-Neural Barrier Disruption - Hui, Flora; Nguyen, Christine T. O.; He, Zheng; Vingrys, Algis J.; Gurrell, Rachel; Fish, Rebecca L.; Bui, Bang V. (Frontiers in Neuroscience, 2017)
To consider whether retinal vasculature leakage may be used as a marker for cortical vascular injury, we compared fluorescein angiography flow dynamics before and after pharmacological disruption of blood-neural barriers. Sodium fluorescein (1%, 200 μl/kg) was intravenously delivered in anaesthetised adult Long Evans rats (n = 44, brain = 18, retina = 26). In the brain cohort, a cranial window was created to allow direct visualisation of surface cortical vessels. Video fluorescein angiography was captured using a rodent retinal camera at 30 frames/second and fluorescence intensity profiles were evaluated for the time to reach 50% brightness (half-rise), 50% decay (half-fall) and the plateau level of remnant fluorescence (offset, %). Cortical vessels fluoresced earlier (artery half-rise: 5.6 ± 0.2 s) and decayed faster (half-fall: 10.3 ± 0.2 s) compared to retinal vasculature. Cortical vessels also had a considerably higher offset, particularly in the capillaries/extravascular space (41.4 ± 2.7%) whereas pigment in the retina reduces such residual fluorescence. In a sub-cohort of animals, sodium deoxycholate (DOC, 0.06 M dissolved in sterile saline, 1 mL) was delivered intravenously to cause simultaneous disruption of the blood-brain and blood-retinal barriers. A separate group received saline as vehicle control. Fluorescein angiography was re-measured at 6 and 24 hours after drug infusion and evaluated by comparing flow dynamics to the upper quartile (75%) of the control group. Retinal vasculature was more sensitive to DOC-induced disruption with a higher fluorescence offset at 6 hours (47.3 ± 10.6%). A delayed effect was seen in cortical vessels with a higher offset evident only at 24 hours (65.6 ± 10.1%). Here we have developed a method to quantitatively compare fluorescein angiography dynamics in the retina and superficial cortical vessels. Our results show that systemic disruption of blood-neural barriers causes vascular leakage in both tissues but earlier in the retina suggesting that pharmacological blood-neural barrier disruption may be detected earlier in the eye than in cortical vasculature.